METHODOLOGICAL COGNITIVE MODEL FOR THE GENERATION AND CONTRIBUTIONS OF SCIENTIFIC RESULTS - Argota Pérez, George (2020)
The possession of integral models that allow to dimension new knowledge continues being a challenge to demonstrate. The purpose of study was to describe a methodological cognitive model for the generation and contribution of scientific results. Through the quantitative technique by content analysis, the proposed model was constructed, which consisted of three processes: 1st) management of scientific information, 2nd) cognitive interpretation; and 3rd) scientific writing. Each process derives recognition structures in a transitional manner, which makes it possible to, the construction towards a validated information. It was concluded that, in any field of research, it is required from the capture of primary information until the new scientific communication achieved as far as the proposed model allowed.